Ecological consequences of increased nitrogen deposition in three northern Great Plains grasslands - Smith, Anine, author; Knapp, Alan, advisor; Symstad, Amy, advisor; Brown, Cynthia, committee member; Kelly, Eugene, committee member (Colorado State University. Libraries, 2012)
Increased nitrogen deposition is an important driver of plant species composition change in terrestrial ecosystems globally. Plant composition change from increased nitrogen inputs can result in substantial species richness declines especially where atmospheric inputs already exceed critical loads. Shifts in community structure can occur through changes in basic ecosystem conditions (such as soil properties) or through alterations in competitive interactions potentially disrupting feedbacks that maintain an ecosystem at a given fertility level. Although there has been a substantial amount of research on the effects of increased N on communities and ecosystems, most studies add large and, relative to natural inputs, unrealistic amounts of N. Thus, responses are often immediate and drastic. This "two-point" approach, comparing control to high-N plots, provides little information about the levels of N inputs at which responses first occur, which is more important for managing and mitigating the effects of increased N deposition in a proactive rather than reactive manner. The overarching goal of this study was to identify response thresholds to N addition in Northern Great Plains grasslands that differed markedly in productivity and soil fertility. Over two years we assessed responses to increased N inputs (from 2.5 to 100 kg N/ha) in soils, leaf tissue, plant community composition, and aboveground net primary production (ANPP) in three northern mixed prairie grasslands that varied 3-fold in ANPP. The results of the study will enable us to better forecast both ecosystem and community responses to increased fertilization in this understudied region. After two years of fertilization (with and without water addition) at levels ranging from 0 to 100 kg N/ha, we found significant effects from increased N inputs on ANPP when nitrogen levels exceeded 68 kg N/ha/year and effects on leaf tissue nitrogen, soil nitrogen content and N mineralization rates, particularly when levels exceeded 45 kg/ha/year. Alterations in soil and leaf nitrogen content and ANPP tended to have linear responses and remained consistent across sites. Significant responses occurred even in low ANPP sites (Badlands NP) which experienced a higher relative response. No significant and consistent effects were found on total species richness, and community metrics such as evenness and diversity indices, plant cover by functional group or canopy cover. Our results suggest that though high fertility and production sites may have a greater absolute biomass response, low fertility and production environments can be quite responsive to nitrogen addition as well. Community change may occur more slowly with these northern grasslands which show little response to two years of increased N inputs.
Keywords: deposition; fertilization; grassland; nitrogen; parks; plains